(untitled) (Research, Society and Development, 2022)
Introduction: Primary Health Care (PHC) aims to provide the first contact with the population, using means for health promotion and disease prevention, working with the same purpose in all municipalities. The PHC has different demands, which influence the work of the teams, the population’s adherence and the users’ knowledge about the service offered in primary care. Objective: to analyze the knowledge of SUS users about the services provided by primary care in the municipality of Itumbiara-GO. Methodology: This is a cross-sectional, exploratory and analytical study. The target audience included all users registered in the Health Units, aged 18 years or older, and the sample consisted of 385 individuals. A structured instrument was used for data collection, consisting of 11 multiple-choice questions applied by the evaluators. Results and discussion: The data showed that 70.4% of respondents are female, who highlight women as major users of the system; 68.30% look for the UBS for non-urgent medical consultations and returns and there was a decrease in the number of people (16.9%) looking for services for prevention and programmatic actions. The bond of these users was demonstrated in the expressive percentage (77.92%), who use the service of the unit they are registered. Conclusion: In view of this, it was evidenced that users had substantial knowledge of primary care, however, still guided by the curative model of diseases.